Increased water‐use efficiency translates into contrasting growth patterns of Scots pine and sessile oak at their southern distribution limits. (15th November 2017) - Martínez‐Sancho, Elisabet; Dorado‐Liñán, Isabel; Gutiérrez Merino, Emilia; Matiu, Michael; Helle, Gerhard; Heinrich, Ingo; Menzel, Annette
Abstract: In forests, the increase in atmospheric CO2 concentrations ( C a ) has been related to enhanced tree growth and intrinsic water‐use efficiency (iWUE). However, in drought‐prone areas such as the Mediterranean Basin, it is not yet clear to what extent this "fertilizing" effect may compensate for drought‐induced growth reduction. We investigated tree growth and physiological responses at five Scots pine ( Pinus sylvestris L.) and five sessile oak ( Quercus petraea (Matt.) Liebl.) sites located at their southernmost distribution limits in Europe for the period 1960–2012 using annually resolved tree‐ring width and δ 13 C data to track ecophysiological processes. Results indicated that all 10 natural stands significantly increased their leaf intercellular CO2 concentration ( C i ), and consequently iWUE. Different trends in the theoretical gas‐exchange scenarios as a response to increasing C a were found: generally, C i tended to increase proportionally to C a, except for trees at the driest sites in which C i remained constant. C i from the oak sites displaying higher water availability tended to increase at a comparable rate to C a . Multiple linear models fitted at site level to predict basal area increment (BAI) using iWUE and climatic variables better explained tree growth in pines (31.9%–71.4%) than in oak stands (15.8%–46.8%). iWUE was negatively linked to pine growth, whereas its effect on growth of oak differed across sites. Tree growth in the western and central oak stands was negatively related to iWUE, whereas BAI from the easternmost stand was positively associated with iWUE. Thus, some Q. petraea stands might have partially benefited from the "fertilizing" effect of rising C a, whereas P. sylvestris stands due to their strict closure of stomata did not profit from increased iWUE and consequently showed in general growth reductions across sites. Additionally, the inter‐annual variability of BAI and iWUE displayed a geographical polarity in the Mediterranean. Abstract : In forests, the increase in atmospheric CO2 concentrations ( C a ) has been related to enhanced tree growth and intrinsic water‐use efficiency (iWUE). However, in drought‐prone areas such as the Mediterranean Basin, it is not yet clear to what extent this "fertilizing" effect may compensate for drought‐induced growth reduction. We investigated tree growth and physiological responses of five Scots pine ( Pinus sylvestris L.) and five sessile oak ( Quercus petraea (Matt.) Liebl.) sites located at their southernmost distribution limits in Europe for the period 1960–2012 using annually resolved tree‐ring width and δ 13 C data to track ecophysiological processes. Our results show that the general increase in iWUE at our study sites has translated into different growth patterns which could be directly linked to the ecophysiology of the two contrasting species.